Epigenetic Reprogramming and Emerging Epigenetic Therapies in CML - Bugler, Jane; Kinstrie, Ross; Scott, Mary T.; Vetrie, David (Frontiers in Cell and Developmental Biology, 2019)
Chronic myeloid leukemia (CML) is a hematopoietic stem cell disorder characterised by BCR-ABL1, an oncogenic fusion gene arising from the Philadelphia chromosome. The development of tyrosine kinase inhibitors (TKIs) to overcome the constitutive tyrosine kinase activity of the BCR-ABL protein has dramatically improved disease management and patient outcomes over the past 20 years. However, the majority of patients are not cured and developing novel therapeutic strategies that target epigenetic processes are a promising avenue to improve cure rates. A number of epigenetic mechanisms are altered or reprogrammed during the development and progression of CML, resulting in alterations in histone modifications, DNA methylation and dysregulation of the transcriptional machinery. In this review these epigenetic alterations are examined and the potential of epigenetic therapies are discussed as a means of eradicating residual disease and offering a potential cure for CML in combination with current therapies.